1832. Epidemiology, risk factors for mortality and resistance associated with Stenotrophomonas maltophilia bacteremia at a tertiary care hospital in Korea over 7 years. (15th December 2022) - Sim, Yong Ki; Lee, Jeong Eun; Lee, Shinwon; Lee, Soon Ok; Hee Lee, Sun
Abstract: Background: Stenotrophomonas maltophilia (SM) is an important emerging nosocomial pathogen. This study aimed to describe the epidemiological, clinical, and microbiological charateristics of SM bacteremia at a tertiary care hospital in Korea over 7 years. Methods: A retrospective study was conducted at a 1150-bed tertiary care hospital in Busan, South Korea. Data were collected between January, 2013 and November, 2019. Results: A total of 79 bacteremia patients (median age: 61 years; 62% males) were reviewed; 38 (48.1%) were in 2013-2016 and 41 (51.9%) were in 2017-2019. The overall SM bacteremia-related 30-days mortality was 31.6%. Susceptibility to levofloxacin, sulfamethoxazole-trimethoprim (SMX/TMP) and minocycline were 87.3%, 92.4% and 100%, respectively. The most common clinical syndrome was central line-associated bloodstream infection (n=37, 46.8%). The others were intra-abdominal infection (n=18, 22.8%), skin and soft tissue infection (n=5, 6.3%) and pneumonia (n=5, 6.3%). In 50.6%, SM was the only pathogen of bacteremia, whereas in 49.4%, more than one causative organisms were isolated. Acinetobacter baumanii (in 8 cases) was the most frequent co-isolated pathogen, followed by Enterococcus faecium (in 6 cases), Pseudomonas aeruginosa (in 5 cases), Staphylococcus epidermidis (in 5 cases), Enterococcus gallinarum (in 3 cases) and Klebsiella pneumoniae (in 3 cases). Age (OR, 6.60; 95% Cl, 1.59-27.41; P = 0.009), inappropriate antimicrobial treatment (OR, 3.47; 95% Cl, 1.14-10.56; P = 0.029), and levofloxacin-resistant strains (OR, 7.86; 95% Cl, 1.20-51.41; P = 0.031) were independent risk factors for SM bacteremia-related 30-days mortality in multivariate analysis. Conclusion: SM bacteremia has a high early mortality rate. In our study, old age, inappropriate antimicrobial treatment and levofloxacin-resistant strains were significant independent risk factors for early mortality in SM bacteremia patients. Early diagnosis and immediate use of appropriate antibiotics are recommended to improve mortality of SM bacteremia. Disclosures: All Authors : No reported disclosures.